Knowledge, practices, and antibiotics use patterns among animal production farmers in Calabar Metropolis - Okon, Aniekanabasi Jonathan; Chibuzor-Eke, Uchechi Esther; Oka, Ibiang Arikpo; Eyam, Lilian Eberechukwu; Akpan, Margaret Inemesit; Inah, Simon Alain (Intelektual Pustaka Media Utama, 2023)
Inappropriate use of antibiotics alongside improper waste/wastewater disposal can contribute to the emergence and dissemination of antibiotic resistance. This research aimed to assess the knowledge, practices, and patterns of antibiotic usage among animal farmers in Calabar Metropolis. Employing a descriptive cross-sectional approach, a structured questionnaire was utilized to elicit information from 137 animal farmers. Data were analysed using SPSS version 25, with Chi-square statistics being employed to ascertain associations between different variables. The findings indicated a high level of knowledge regarding antibiotic use and the repercussions following its misuse on the environment, with 74.5% exhibiting high levels of knowledge. Majority (92.7%) of the respondents used antibiotics for various purposes in the farm. About 55% of respondents who used antibiotics had training on antibiotics use. Majority (79.6%) of the respondents had poor waste/wastewater disposal practices. Associations were found between farmers’ knowledge level on antibiotic resistance and level of antibiotics use (p=0.031). Moderate antibiotic use was more among farmers with high knowledge level. An association was also found between farmers’ training on antibiotics use and farmers’ level of antibiotics use (p=0.043). Mandatory and targeted training for animal production farmers on proper and judicious antibiotic use is expedient to safeguard public health.